Trion confinement in monolayer MoSe2 by carbon nanotube local gating. (1st January 2023) - Hotta, Takato; Nakajima, Haruna; Chiashi, Shohei; Inoue, Taiki; Maruyama, Shigeo; Watanabe, Kenji; Taniguchi, Takashi; Kitaura, Ryo
Abstract: We have successfully confined trions into a one-dimensional restricted space of a MoSe2 device with carbon nanotube (CNT) gate electrodes. The dry transfer process, including deterministic dry transfer of aligned CNTs, has led to an hBN-encapsulated MoSe2 device with CNT back gate electrodes. In contrast to a location without CNT gate electrodes, applying voltage via CNT gate electrodes significantly alters PL spectra at a location with CNT gate electrodes. PL imaging has revealed that image contrast from trions is linear along the CNT electrode underneath, consistent with 1D confinement of trions in response to the CNT local gating. The confinement width obtained from the PL image is 5.5 × 10 2 nm, consistent with nanoscale 1D confined trions with the diffraction limit broadening. This work has demonstrated electrical control of excitonic states at the nanoscale, leading to novel optoelectronic properties and exciton devices in the future.